(untitled) (Research, Society and Development, 2021)
This article is based on the judicialization of access to services of high and medium complexity of the Brazilian Unified Health System (SUS), thus considering the lawsuits filed against the SUS asking for services that demand high technological density and/or demand for expertise and special skills above average standards, with low relative frequency; and with high unit cost and / or treatment. Initiated through a bibliographic review, using inductive reasoning, the developed work seeks to expose the inefficiency and omission of the Unified Health System by assessing the results of studies referring to judicial demands that affect the right to health, considering that the need for intervention in this matter reflects the failure in the administrative way to comply with the constitutional protection of the right to health, strongly supported in the Brazilian legal system, from the Brazilian Constitution to the infraconstitutional rules and administrative acts of the organs that are part of the Unified Health System, as well as of complementary form, in the private initiative.